If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + 13 = 15 Reorder the terms: 13 + 4t = 15 Solving 13 + 4t = 15 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 4t = 15 + -13 Combine like terms: 13 + -13 = 0 0 + 4t = 15 + -13 4t = 15 + -13 Combine like terms: 15 + -13 = 2 4t = 2 Divide each side by '4'. t = 0.5 Simplifying t = 0.5
| 4x+19=14x-101 | | -22=-8y+2(y-8) | | -7v+8=19 | | 8x-11=5x+1 | | 5(y-1)-5=45 | | -4(x+2)=4x+-8 | | -4(x+2)=4x+8 | | 7(2n-3)=5(3n-4) | | -17=4x-6 | | 10x+9=6x+25 | | 10x-22=68 | | x^2+x+2+x+2=100 | | x(x-5)=36 | | 4x^2-6x+2=0 | | 3(n+2)+4n=4(n+2)+4 | | 41+2(3x+6)=95 | | 2(3)-2(4x)+7=0 | | (2*a)+17= | | 3(n+2)-2=4(n-4)-4(n-11) | | 118-(3*b)= | | x(x-8)=-15 | | -3x^2+36x-72=0 | | 25x^2=100 | | 8(2x-1)=72 | | X+46=72 | | 5d-3.3=7.5 | | 17x-8x-9=76-40 | | n=15+2m-4 | | 5(3c-c)+3=43 | | (3x+2)(x+1)=4 | | 2w+9w+2w+8w+7w+w= | | 4a-2=7a-6 |